Moisture transport to British Columbia’s upper Nechako Watershed associated with three atmospheric rivers - Tamar S. Richards-Thomas; Stephen J. Déry (Discover Atmosphere)
Abstract Atmospheric rivers (ARs) that reach British Columbia’s (BC’s) Coast Mountains undergo orographic lifting, leading to intense precipitation that impacts the region’s hydroclimatology. To assess the impact of ARs on the upper Nechako Watershed, the Tahtsa Ranges Atmospheric River Experiment (TRARE) collected detailed hydrometeorological data in this region during September and October 2021. For three case studies, primary pathways of moisture transport, water vapor budgets, and constancy of moisture transport across the upper Nechako Watershed are identified and quantified using TRARE observational and ERA5 reanalysis datasets. ARs associated with Events 3 and 5 had a southwest-to-northeast path with minimal temporal moisture variability. In contrast, Event 10 primarily followed a southeasterly-to-northwesterly pathway exhibiting more variable moisture transport. Although Events 3 and 5 are associated with weak ARs and Event 10 is indirectly linked to bombogenesis, they all contributed similar amounts (~ 109 kg s−1) to the water vapor budget for the upper Nechako. Additionally, stronger winds and higher steadiness of moisture transport are associated with copious precipitation across the upper Nechako, particularly along the basin’s southern and western boundaries. ARs that impact the upper Nechako therefore play a crucial role in replenishing water resources that sustain ecological systems, aquatic habitat, hydropower generation, and domestic water consumption.